Analisis Pengendalian Pesediaan Bahan Baku dengan Menggunakan Metode Economic Order Quantity (EOQ) pada Perusahaan Roti Bonansa - fajrin, Eldwidho hanarista; Slamet, Achmad (Management Analysis Journal, 2016)
ABSTRACT Fajrin, Eldwidho Hanarista. 2015. â€œAnalisis Pengendalian Persediaan Bahan Baku Dengan Menggunakan Metode Economic Order Quantity (EOQ) Pada Perusahaan Roti Bonansaâ€. Manajemen Keuangan. Fakultas Ekonomi. Universitas Negeri Semarang. Pembimbing Prof. Dr. H. Achmad Slamet, M.Si Key Word : Economic Order Quantity (EOQ), Raw Material Supply, Safety Stock (SS), Reorder Point (ROP), Total Inventory Cost (TIC) Optimal of raw material supply is an important factor in the fluency of the production process in a company. These raw materials can be controlled by using certain methods, one of that is a Economic Order Quantity (EOQ) method which has a better level of calculation accuracy than conventional methods. This study is quantitative research, which has a goal to examine more deeply about the use of methods Economic Order Quantity (EOQ) in the control of raw materials companies Bread bonanza. The object of this study is the number of purchases, the amount of inventories, amount of usage of raw materials used in production, as well as a booking fee and the cost of storage of raw materials. The result showed the optimal inventory of raw flour materials using EOQ method is 3009kg with a frequency of purchase as 30 times, safety stock is 504kg and ROP done at the time the raw material warehouse at 1188kg and TIC Rp 12,559,196.00. Optimal supplies of sugar with EOQ method is 1244 kg, with a frequency of purchase as 20 times, safety stock is 412 kg and ROP should be done at the time the raw material warehouse is 578kg while the TIC Rp3.461.934,00. Conclusions from this research is the calculation method of EOQ in counting raw materials wheat flour and sugar more efficiently than with conventional methods. This can be prove from the results of the comparison TIC more efficient use EOQ method to save costs and is able to increase profits. Suggestions for management of Bonansa company is to use EOQ method in process of controlling raw materials companies.